SOSIALISASI STRATEGI PERENCANAAN SUMBER DAYA MANUSIA UNTUK MENDUKUNG KREATIVITAS SISWA DALAM MENINGKATKAN JIWA KEWIRAUSAHAAN DI SMA NEGERI 5 KOTA SERANG - Darma Jata, Anak Agung Gede; Susanto, Denies; Rahmawati, Irma (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
The objective of the Community Service Program is to implement one of the Three Pillars of Higher Education (Tri Dharma Perguruan Tinggi). Additionally, it is expected that through this community service, the presence of higher education institutions can make a significant contribution to the development and application of knowledge in society. Therefore, this community service activity aims to provide socialization regarding human resource (HR) planning strategies to enhance students' creativity and foster an entrepreneurial mindset from an early age. The methods used in this activity include interactive socialization, group discussions, and hands-on practice through a project-based learning approach. The socialization sessions consist of presentations on the importance of creativity in business, HR management strategies in entrepreneurship, and techniques for developing simple business ideas. Group discussions are conducted to encourage students to explore their creative ideas, while hands-on practice sessions aim to train them in entrepreneurial skills through business simulations. The results of the activity indicate a significant improvement in students' understanding of entrepreneurial concepts. Students became more motivated to explore their own business ideas and understand the importance of creativity in building a sustainable business. The positive impact of this program is reflected in the increased interest of students in entrepreneurship and their readiness to innovate in creating business opportunities. Furthermore, it is expected that schools will develop more entrepreneurship-based programs to shape a generation that is more creative and independent. Thus, this community service program is expected to serve as a model that can be implemented in other schools to build more effective HR planning strategies in supporting students' creativity and entrepreneurial mindset.